Tuning mechanical reinforcement and bioactivity of 3D printed ternary nanocomposites by interfacial peptide-polymer conjugates. (12th June 2019) - Bas, Onur; Hanßke, Felix; Lim, Jing; Ravichandran, Akhilandeshwari; Kemnitz, Erhard; Teoh, Swee-Hin; Hutmacher, Dietmar W; Börner, Hans G
Abstract: We present a study on ternary nanocomposites consisting of medical grade poly(ε-caprolactone) (mPCL) matrix, hydroxyapatite nanopowder (nHA) and compatibilized magnesium fluoride nanoparticle (cMgF2 ) fillers. MgF2 nanoparticles were compatibilized by following a design approach based on the material interfaces of natural bone. MgF2 -specific peptide-poly(ethylene glycol) conjugates were synthesized and used as surface modifiers for MgF2 nanoparticles similarly to the non-collagenous proteins (NPC) of bone which compatibilize hydroxyapatite nanocrystallites. Different compositions of mPCL/nHA/cMgF2 composites were blended together and processed into three dimensional (3D) scaffolds using solvent-free techniques including cryomilling and melt extrusion-based additive manufacturing. The use of two different inorganic fillers in mPCL resulted in nanocomposite materials with enhanced mechanical and biological properties. In particular, cMgF2 nanoparticles were found to be the primary constitent leading to the significant improvements in the mechanical properties of these composites. The scaffolds of the ternary nanocomposites provided the best in vitro performance in terms of osteogenic differentiation and stimulated mineralization. In summary, we demonstrated that the concept of bioinspired interface engineering facilitates the development of homogeneous ternary nanocomposites with increased processability in additive biomanufacturing. Additionally, the concept leads to scaffolds exhibiting enhanced mechanical and biological properties. Overall, these multicomponent nano-interfaced building blocks add a new group of advanced functional materials with tunable mechanical properties, degradation and bioactivity.